If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 23 = 3x Reorder the terms: 23 + 2x = 3x Solving 23 + 2x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 23 + 2x + -3x = 3x + -3x Combine like terms: 2x + -3x = -1x 23 + -1x = 3x + -3x Combine like terms: 3x + -3x = 0 23 + -1x = 0 Add '-23' to each side of the equation. 23 + -23 + -1x = 0 + -23 Combine like terms: 23 + -23 = 0 0 + -1x = 0 + -23 -1x = 0 + -23 Combine like terms: 0 + -23 = -23 -1x = -23 Divide each side by '-1'. x = 23 Simplifying x = 23
| -8+30+-9= | | 11+n=27 | | 6*x-2*x=520 | | x-2*6*x=520 | | sin(x)+5x=0 | | x=5log(x) | | x-2*y=520 | | x*x-9x=-18 | | x-5log(x)=0 | | 9=-3(2b+7) | | 2x^2w^5*8x*2w^4= | | 6x+30=2x+10 | | 2x^2+3x-4=8x-4 | | 3ab*2cd=4ac | | 5(3a-2)=50 | | 2x*2x=4x | | (M+3)x^2+2m(x+1)+3=0 | | sqrt(4x+8)+7=4x | | 16-2(x-1)=x | | 4x-6x-6=3+14 | | 8x+24=6x+40 | | -1/4=1/5b | | 11(x-8)-8=28x-232 | | -1/4=1/5 | | 5x+9=1x+17 | | ln(x)+10x=4 | | 3x/7+4/5=6/7 | | 5(4x+9)= | | -a+b=1800 | | 1/7(7x-6)=-9/2-7/2 | | lnx+10x=4 | | -4[16+(-12)]= |